A state-of-the-art of industrial sustainability: definitions, tools and metrics. (18th February 2010) - Arena, Marika; Ciceri, Natalia Duque; Terzi, Sergio; Bengo, Irene; Azzone, Giovanni; Garetti, Marco
At present, a wide range of stakeholders including consumers, regulators, shareholders and public bodies are demanding that companies address sustainability in a more comprehensive way. However, even if a company actually wishes to innovate its processes for improving the way to account for sustainability, it will face relevant difficulties to deal with different guidelines, tools and methods currently addressing the matter from various points of view. The purpose of this paper is to review and synthesise literature on sustainability from an operational point of view with the objective to help companies to answer to three main questions: What is sustainability? (How it has been defined), How can sustainability of processes and products be achieved and measured? (What are the different existing means and indicators) and How can they be improved? In such a context, this paper investigates and debates the role of technological development, as an enabling factor of sustainability within the companies.